Modelling and analysis of LRRK2 mutations in iPSC-derived dopaminergic neurons and astrocytes - Booth, H (2017)
Parkinson's disease (PD) is a common neurodegenerative disorder, characterised by preferential loss of ventral midbrain dopaminergic (vmDA) neurons in the substantia nigra pars compacta (SNc). The majority of PD cases have unknown aetiology; however, between 5-10% arise due to known genetic mutations, the most common of which are found in the LRRK2 gene. LRRK2 is expressed in neurons and glia in the human brain; therefore, cell-autonomous and/or non-cell autonomous effects may participate in LRRK2-mutation-mediated degeneration of vmDA neurons. This study set out to understand the effects of LRRK2 mutations on human vmDA neurons and midbrain astrocytes, and to shed new light on the mechanisms of PD pathogenesis. To achieve this goal, differentiation protocols were generated to produce vmDA neurons and midbrain patterned (MP) astrocytes from induced pluripotent stem cells (iPSCs). iPSCs from patients carrying the LRRK2-G2019S mutation were differentiated into both cell types, and hypothesis-driven analysis of cellular functions including autophagy, mitochondrial respiration, glycolysis, and cellular migration was conducted; however, no disease phenotypes were observed. Following this, proteomics and transcriptomics techniques were then used to analyse the effects of the LRRK2-G2019S mutation in an unbiased manner. In the iPSC-derived MPastrocyte cultures, this technique highlighted stochastic X-chromosome reactivation events that led to difficulties in interpreting the resulting data; however, in the iPSC-derived vmDA-neuron cultures, LRRK2-G2019S-mediated inhibition of endocytosis and axon guidance was identified. These findings were found to be consistent in iPSC-derived vmDA-neuron cultures carrying the LRRK2-R1441C mutation, suggesting that these two mutations exert their pathogenic effects through similar mechanisms. Finally, phosphoproteomics analysis of iPSC-derived vmDA-neuron cultures was conducted to identify bone fide LRRK2-kinase substrates. Eleven potential LRRK2- kinase substrates were identified, nine of which have been previously shown to participate in endocytic vesicle trafficking, neurite outgrowth, and synaptic function. The findings of this study suggest that LRRK2 has neuron-specific functions, and that its mutations contribute to neurodegeneration in a cell-autonomous manner.